Hollenberg Station, Washington County - Rhodes, Ashley (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author tells the colorful history of the Hollenberg station and the Hollenberg family. The station provided an essential stopping point for settlers, soldiers, Pony Express riders, and shipping trains.
Ashley Rhodes, “Hollenberg Station, Washington County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/78.
Keywords: Washington County; Fort Riley; Mormon Trail; William B. Waddell; Kanza Indians; Bigelow Station